Pengembangan Media Pembelajaran Ular Tangga MEKUHI (Merah, Kuning, Hijau) pada Operasi Hitung Perkalian di Kelas IV SD Putra Bangsa Driyorejo - Hermawan, Nadya Sapta; Bahtiar, Reza Syehma; Jarmani, Jarmani (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to develop a snake and ladder learning media for multiplication operations in the fourth grade of SD Putra Bangsa Driyorejo. The research method used is Research and Development (R&D). In this research and development process, the procedure applied follows the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques used include observation, interviews, and student assessments. The resulting data were analyzed descriptively quantitatively and qualitatively. Based on the analysis results, the MEKUHI snake and ladder learning media can facilitate students' understanding of the material. The results of this study indicate that (1) the MEKUHI snake and ladder learning media is appropriately developed and feasible to use, as it aligns with the learning objectives, and (2) the MEKUHI snake and ladder learning media can help students understand the material more easily and increase student engagement in the classroom.